Characteristics of preparatory sequence against different shoot patterns by elite soccer goalkeepers - Matsukura, K.; Hirashima, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2020)
The aim of this study is to shed light on preparatory sequence against shots by elite goalkeepers in response to variations in the position from where a shot at goal is taken and in the number of touches ahead of the shot. The samples were extracted from videos of shots in all 64 matches of the 2018 FIFA World Cup in Russia. First, to analyse the characteristics of shots in elite games, the results of shots from different areas and after different numbers of touches were analysed. Next, to analyse preparatory sequence by goalkeepers to defend the shots, the shots were classified into six groups, based on observation of `the presence or absence of specific prejump`, `change in the distance between the feet during the preparation period, and `whether the goalkeeper was still in moving position or had completed the move`. As a result of this analysis, first, as a characteristic of the elite game, it was possible to divide positions from where shots were taken in two types of areas, based on the probability of the shot being on target and the probability that a goal would be scored. In addition, it was shown to be possible that, when they are on target, one-touch shots are hard for goalkeepers to defend. Next, as an overall trend, the most frequent preparatory sequence by goalkeepers was to prepare for the shot with a slight jump to widen the distance between the feet after they had finished moving their position. In addition, when looking at the breakdown of preparatory sequence for different numbers of touches ahead of the shot, it was found that the proportion of goalkeepers moving their position until immediately before the shot rose for one-touch shots. As a result of all these analyses, it was concluded that elite goalkeepers must engage in different preparatory sequence, depending on the circumstances of the shot.